A comparison between molecular and serological methods in the detection of Bovine Brucella species - Nkomo, Zanele (Midlands State University, 2017)
Bovine brucellosis is endemic in Zimbabwe and is an important veterinary disease, responsible for large losses in livestock through abortions and still-born calves. It is also a zoonotic disease and as such poses a threat to public health. For this reason, it is important for every farmer to know the status of their herd. This study was carried out to compare the reliability of serological tests with molecular test in the detection of bovine brucellosis. A total of 17 whole blood and serum samples were collected from a herd of cattle in Matabeleland that had previously been vaccinated. This study was conducted in July 2015. The serum samples were tested for brucellosis serologically using the Complement Fixation test (CFT). DNA was extracted from the whole blood samples and the Polymerase Chain Reaction (PCR) was used to test for Brucella using Brucella specific primers. Test results from serological and molecular methods were then compared. Serological tests showed that all samples were positive for brucellosis using CFT. Using molecular methods, only 12 samples were found positive while 5 samples were negative for the Brucella bacteria. In this study, it was possible to differentiate the species as well as the biovars of Brucella using PCR which was not possible using serological techniques. Samples that were positive for Brucella were either B. abortus biovars (1, 2, 4) which produced a 100 bp and 498 bp bands or B. abortus biovars (3, 5, 6, 9) / B. suis (2, 3, 4, 5) which produced a 100 bp band. Further differentiation between B. abortus (3, 5, 6, 9) and B. suis (2, 3, 4, 5) could not be done due to a limitation in laboratory resources. The study confirms PCR to be a more reliable and specific tool for the detection of Brucella spp. when compared to the conventional CFT method of detecting brucellosis used in Zimbabwe. The use/adoption of PCR as a confirmatory test in the testing of Brucellosis is recommended in this study.